Adherence to Antihypertensive Medication in Treatment-Resistant Hypertension Undergoing Renal Denervation - Schmieder, Roland; Ott, Christian; Schmid, Andrea; Friedrich, Stefanie; Kistner, Iris; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Toennes, Stefan W. (Journal of the American Heart Association, 2016)
Adherence to medication has been repeatedly proposed to represent a major cause of treatment-resistant hypertension (TRH); however, treatment decisions such as treating TRH with renal denervation depend on accurate judgment of adherence. We carefully analyzed adherence rates to medication before and after renal denervation and its effect on blood pressure (BP) control.Eighty patients with TRH were included in 2 prospective observational studies that assessed the difference of potential antihypertensive and nephroprotective effects of renal denervation. To compare prescribed with actual medication intake (representing a measure of adherence), we analyzed urine samples collected at baseline and at 6 months after renal denervation for antihypertensive compounds or metabolites (by liquid chromatography-mass spectrometry). In addition to office BP, 24-hour ambulatory BP and central hemodynamics (central systolic pressure, central pulse pressure) were assessed. Informed consent for analyses of urine metabolites was obtained from 79 of 80 patients. Actual intake of all antihypertensive drugs was detected at baseline and at 6 months after renal denervation in 44 (56%) and 52 (66%) patients, respectively; 1 drug was missing in 22 (28%) and 17 (22%) patients, respectively, and >=2 drugs were missing in 13 (16%) and 10 (13%) patients, respectively. At baseline, 24-hour ambulatory BP (P=0.049) and central systolic BP (P=0.012) were higher in nonadherent patients. Adherence did not significantly change overall (McNemar-Bowker test, P=0.362). An increase in adherence was observed in 21 patients, and a decrease was observed in 11 patients. The decrease in 24-hour ambulatory BP was not different in those with stable adherence 6 months after renal denervation (n=41, -7±13 mm Hg) compared with those with increased adherence (n=21, -10±13 mm Hg) and decreased adherence (n=11, -7±14 mm Hg) (P>0.20). Our study is limited by the relatively small sample size and potentially by the specific health environment of our university center (Northern Bavaria, Germany).Nonadherence to medication among patients with TRH was relatively low: ?1 of 6 patients with TRH did not take >=2 of the prescribed drugs. Adherence pattern did not change significantly after renal denervation and had no impact on the overall observed BP changes, supporting the concept that renal denervation is an effective treatment in patients with TRH.URL: https://www.clinicaltrials.gov. Unique identifiers: NCT00888433, NCT01442883 and NCT01687725.
EVALuna2:3842

Afferent Nerve Fibers of the Skin - Influence of salt intake - Ditting, Tilmann; Rodionova, Kristina; Reeh, Peter; Eberhardt, Miriam; Veelken, Roland (FASEB JOURNAL, 2020)
CRIS-Team WoS Importer:2020-10-16

Afferent neurons of the kidney with impaired firing pattern in inflammation – role of sodium currents? - Lale, Nena; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Pflügers Archiv: European Journal of Physiology, 2023)
Peripheral neurons with renal afferents exhibit a predominantly tonic firing pattern of higher frequency that is reduced to low frequencies (phasic firing pattern) in renal inflammation. We wanted to test the hypothesis that the reduction in firing activity during inflammation is due to high-activity tonic neurons switching from higher to low frequencies depending on altered sodium currents. We identified and cultivated afferent sensory neurons with renal projections from the dorsal root ganglia (Th11-L2). Cultivated neurons were incubated with the chemokine CXCL1 (1,5 nmol/ml) for 12 h. We characterized neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., < 5 APs upon stimulation in the current clamp. Their membrane currents were investigated in a voltage clamp. Data analyzed: renal vs. non-renal and tonic vs. phasic neurons. Renal afferent neurons exposed to CXCL1 showed a decrease in tonic firing pattern (CXCL1: 35,6% vs. control: 57%, P < 0.05). Na+ and K+ currents were not different between control renal and non-renal DRG neurons. Phasic neurons exhibited higher Na+ and K+ currents than tonic resulting in shorter APs (3.7 ± 0.3 vs. 6.1 ± 0.6 ms, P < 0.01). In neurons incubated with CXCL1, Na+ and K+ peak current density increased in phasic (Na+: − 969 ± 47 vs. − 758 ± 47 nA/pF, P < 0.01; K+: 707 ± 22 vs. 558 ± 31 nA/pF, P < 0.01), but were unchanged in tonic neurons. Phasic neurons exposed to CXCL1 showed a broader range of Na+ currents ([− 365– − 1429 nA] vs. [− 412– − 4273 nA]; P < 0.05) similar to tonic neurons. After CXCL1 exposure, significant changes in phasic neurons were observed in sodium activation/inactivation as well as a wider distribution of Na+ currents characteristic of tonic neurons. These findings indicate a subgroup of tonic neurons besides mere tonic or phasic neurons exists able to exhibit a phasic activity pattern under pathological conditions.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Chemokine; Firing pattern; Phasic; Renal afferent nerve; Sodium currents; Tonic; Voltage-gated sodium channels

Afferent renal innervation in anti-Thy1.1 nephritis in rats - Rodionova, Kristina; Veelken, Roland; Hilgers, Karl Friedrich; Paulus, Eva Maria; Linz, Peter; Fischer, Michael J.M.; Schenker, Martina; Reeh, Peter; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; et al. (American Journal of Physiology-Renal Physiology, 2020)
Afferent renal nerves exhibit a dual function controlling central sympathetic outflow via afferent electrical activity and influencing intrarenal immunological processes by releasing peptides such as calcitonin gene-related peptide (CGRP). We tested the hypothesis that increased afferent and efferent renal nerve activity occur with augmented release of CGRP in anti-Thy1.1 nephritis, in which enhanced CGRP release exacerbates inflammation. Nephritis was induced in Sprague-Dawley rats by intravenous injection of OX-7 antibody (1.75 mg/kg), and animals were investigated neurophysiologically, electrophysiologically, and pathomorphologically 6 days later. Nephritic rats exhibited proteinuria (169.3 ± 10.2 mg/24 h) with increased efferent renal nerve activity (14.7 ± 0.9 bursts/s vs. control 11.5 ± 0.9 bursts/s, n = 11, P < 0.05). However, afferent renal nerve activity (in spikes/s) decreased in nephritis (8.0 ± 1.8 Hz vs. control 27.4 ± 4.1 Hz, n = 11, P < 0.05). In patch-clamp recordings, neurons with renal afferents from nephritic rats showed a lower frequency of high activity following electrical stimulation (43.4% vs. 66.4% in controls, P < 0.05). In vitro assays showed that renal tissue from nephritic rats exhibited increased CGRP release via spontaneous (14 ± 3 pg/mL vs. 6.8 ± 2.8 pg/ml in controls, n = 7, P < 0.05) and stimulated mechanisms. In nephritic animals, marked infiltration of macrophages in the interstitium (26 ± 4 cells/mm2) and glomeruli (3.7 ± 0.6 cells/glomerular cross-section) occurred. Pretreatment with the CGRP receptor antagonist CGRP8-37 reduced proteinuria, infiltration, and proliferation. In nephritic rats, it can be speculated that afferent renal nerves lose their ability to properly control efferent sympathetic nerve activity while influencing renal inflammation through increased CGRP release.
CRIS-Team Scopus Importer:2020-11-13
Keywords: afferent renal neerves; calcitonin gene-related peptide; renal inflammation; renal innervation; sympathetic innervation

AT II Receptor Blockade and Renal Denervation: Different Interventions with Comparable Renal Effects? - Rodionova, Kristina; Hindermann, Martin; Hilgers, Karl Friedrich; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Kidney & Blood Pressure Research, 2021)
Background: Angiotensin II (Ang II) and the renal sympathetic nervous system exert a strong influence on renal sodium and water excretion. We tested the hypothesis that already low doses of an Ang II inhibitor (candesartan) will result in similar effects on tubular sodium and water reabsorption in congestive heart failure (CHF) as seen after renal denervation (DNX). Methods: Measurement of arterial blood pressure, heart rate (HR), renal sympathetic nerve activity (RSNA), glomerular filtration rate (GFR), renal plasma flow (RPF), urine volume, and urinary sodium. To assess neural control of volume homeostasis, 21 days after the induction of CHF via myocardial infarction rats underwent volume expansion (0.9% NaCL; 10% body weight) to decrease RSNA. CHF rat and controls with or without DNX or pretreated with the Ang II type-1 receptor antagonist candesartan (0.5 ug i.v.) were studied. Results: CHF rats excreted only 68 + 10.2% of the volume load (10% body weight) in 90 min. CHF rats pretreated with candesartan or after DNX excreted from 92 to 103% like controls. Decreases of RSNA induced by volume expansion were impaired in CHF rats but unaffected by candesartan pointing to an intrarenal drug effect. GFR and RPF were not significantly different in controls or CHF. Conclusion: The prominent function of increased RSNA - retaining salt and water - could no longer be observed after renal Ang II receptor blockade in CHF rats.
CRIS-Team WoS Importer:2021-06-11
Keywords: Renal sympathetic innervation; Angiotensin II; Congestive heart failure; Renal nerve ablation; Renal function

Central processing of afferent renal pathways—significance and implications - Rodionova, Kristina; Veelken, Roland (Pflügers Archiv: European Journal of Physiology, 2020)
CRIS-Team Scopus Importer:2020-09-25

Central pulse pressure predicts BP reduction after renal denervation in patients with treatment-resistant hypertension - Ott, Christian; Schmid, Axel; Toennes, Stefan W.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (EuroIntervention, 2015)
Enhanced vascular ageing is associated with elevated central pulse pressure (cPP), an independent predictor of cardiovascular (CV) events. Although antihypertensive treatment strategies are effective, high residual CV risk remains indicative of advanced and largely irreversible vascular damage. Renal denervation (RDN) has been shown to reduce blood pressure (BP) to various extents in patients with treatment-resistant hypertension (TRH). We hypothesised that cPP predicts BP reduction after RDN.Sixty-three patients with true TRH underwent catheter-based RDN using the Symplicity Flex(TM) catheter and were followed for six months. At baseline, cPP was assessed by pulse wave analysis (SphygmoCor(TM)). Patients were stratified according to their median cPP (55 mmHg), and called "low cPP" (below the median) or "high cPP" (above the median). Office BP reduction six months after RDN was greater (-22±19/-13±11 vs. -12±20/-5±13 mmHg, p=0.038/0.014) and 24-hr ambulatory blood pressure (ABP) reduction tended to be greater (-11±13/-8±10 vs. -3±18/-4±10 mmHg, p=0.070/0.112) in patients with low cPP compared to those with high cPP. Only cPP (?=0.687, p=0.001) and baseline systolic BP (?=-0.564, p<0.001) were independent determinants of office systolic BP reduction after RDN.Our data suggest that cPP, indicative of the degree of large arterial stiffening, may be helpful to identify responders to RDN.
EVALuna2:3764

Circadian rhythm and day to day variability of serum potassium concentration: a pilot study - Schmidt, Stefan; Ditting, T.; Deutsch, Birgit; Schutte, R.; Friedrich, S.; Kistner, I.; Ott, Christian; Raff, U.; Veelken, Roland; Schmieder, Roland (Journal of Nephrology, 2015)
Hyperkalemia is a common and life-threatening complication frequently seen in patients with acute kidney injury, end-stage renal disease and chronic heart failure. Cardiac arrest and ventricular fibrillation are possible consequences. Biosensors are currently being developed to measure serum potassium under ambulatory conditions and trigger an alarm if the potassium concentration exceeds normal limits. Only few studies exist on the circadian rhythm of potassium; and its dependence on age and kidney function is less clear.Our observational monocentric exploratory study included 30 subjects of which 15 had impaired renal function (RF) (GFR <60 ml/min/1.73 m(2)). Subjects were further categorized into three age groups: 18-39 years (N normal RF = 5, N impaired RF = 4), 40-59 years (N normal RF = 5, N impaired RF = 6), 60-80 years (N normal RF = 5, N impaired RF = 5). Serum potassium levels were measured every 2 h during a 24 h period and repeated once after 2, 4, or 6 days.In the 15 subjects with normal RF, the lowest mean potassium level (3.96 ± 0.14 mmol/l) was observed at 9 p.m. and the greatest (4.23 ± 0.23 mmol/l) at 1 p.m. In patients with impaired RF the lowest mean potassium level (4.20 ± 0.32 mmol/l) was observed at 9 p.m. and the highest (4.57 ± 0.46 mmol/l) at 3 p.m. The range between the mean of minimum and maximum was greater in patients with impaired RF (0.71 ± 0.45 mmol/l) than in subjects with normal RF (0.53 ± 0.14 mmol/l) [p < 0.001]. No difference in the circadian rhythm was found between the first and second examination.Our results indicate that patients with normal and impaired RF have comparable circadian patterns of serum potassium concentrations, but higher fluctuations in patients with impaired RF. These results have clinical relevance for developing an automatic biosensor to measure the potassium concentration in blood under ambulatory conditions in patients at high risk for potassium fluctuations.
EVALuna2:3700

Complex reinnervation pattern after unilateral renal denervation in rats - Rodionova, Kristina; Fiedler, Christian; Günther, Franziska; Grouzmann, Eric; Neuhuber, Winfried; Fischer, Michael; Ott, Christian; Linz, Peter; Freisinger, Wolfgang; Heinlein, Sonja; Schmidt, Stefan; Schmieder, Roland; et al. (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2016)
Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature. DNX kidneys and nondenervated kidneys were examined 1, 4, and 12 wk after DNX. Tissue levels of CGRP and norepinephrine (NE) were measured with ELISA and mass spectrometry, respectively. DNX decreased TH and CGRP labeling by 90% and 95%, respectively (P < 0.05) within 1 wk. After 12 wk TH and CGRP labeling returned to baseline with a shift toward afferent innervation (P < 0.05). Nondenervated kidneys showed a doubling of both labels within 12 wk (P < 0.05). CGRP content decreased by 72% [3.2 ± 0.3 vs. 0.9 ± 0.2 ng/gkidney; P < 0.05] and NA by 78% [1.1 ± 0.1 vs. 0.2 ± 0.1 pmol/mgkidney; P < 0.05] 1 wk after DNX. After 12 wk, CGRP, but not NE, content in DNX kidneys was fully recovered, with no changes in the nondenervated kidneys. The use of phenol in the DNX procedure did not influence this result. We found morphological reinnervation and transmitter recovery of afferents within 12 wk after DNX. Despite morphological evidence of sympathetic regrowth, NE content did not fully recover. These results suggest a long-term net surplus of afferent influence on the DNX kidney may be contributing to the blood pressure lowering effect of DNX.
EVALuna2:3840

COPEPTIN AS A RESEARCH MARKER IN CARDIOVASCULAR DISEASE - Bosch, Agnes; Ott, C.; Schmid, Andrea; Kannenkeril, Dennis; Karg, M.; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2018)
EVALuna2:202963

COPEPTIN LEVELS IN PATIENTS WITH TREATMENT RESISTANT HYPERTENSION BEFORE AND AFTER RENAL DENERVATION - Jumar, A.; Ott, Christian; Schmid, Axel; Kannenkeril, Dennis; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36267

Copeptin levels in patients with treatment resistant hypertension before and six months after renal denervation - Bosch, Agnes; Schmid, Axel; Ott, Christian; Kannenkeril, Dennis; Karg, Marina V.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (American Journal of Hypertension, 2019)
BACKGROUND: Copeptin, the C-terminal peptide of pro-vasopressin, is released from the neurohypophysis and reflects the activity of the hormone arginine vasopressin in patients with hypertension. Elevated copeptin levels are associated with increased cardiovascular and all-cause mortality. The aim of this study is to compare copeptin levels in patients with treatment resistant hypertension (TRH) before and 6 months after renal denervation (RDN). METHODS: Copeptin was measured in 34 patients with TRH and 30 patients with primary hypertension stage 1 or 2 (HT). In addition, copeptin levels were measured in patients with TRH at 6 month follow-up visit after RDN. RDN was performed by an experienced interventionalist applying at least four ablations longitudinally and rotationally within the lengths of each renal artery to cover a full four quadrant ablation. RESULTS: In patients with TRH 24h ambulatory blood pressure (BP) decreased from 154±15/ 87±12 mmHg to 146±13/ 83±7.9 mmHg after RDN (systolic: p=0.001, diastolic: p=0.034). There was no significant change in copeptin levels in these 34 patients with TRH before versus six months after RDN (median 8.4 [interquartile range 3.6-14] vs 8.5 [4.5-13] pmol/l, p=0.334). Patients with TRH had higher copeptin levels (p=0.024) than patients with HT (24h ambulatory BP: 142±11/ 91±8.3 mmHg, copeptin: 4.2 [2.8-6.3] pmol/l). CONCLUSION: Patients with TRH showed 2 fold higher copeptin levels than patients with HT. RDN did not lead to any change of copeptin levels in patients with TRH 6 months after procedure despite significant fall in BP.
EVALuna2:210911

Correlations Between Interleukin-11 Expression and Hypertensive Kidney Injury in a Rat Model of Renovascular Hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Dambietz, Thomas; Veelken, Roland; Amann, Kerstin Ute; Hartner, Andrea; Hilgers, Karl Friedrich (American Journal of Hypertension, 2020)
BACKGROUND: Interleukin-11 (IL-11) is a pleiotropic cytokine of the interleukin-6 family. Recent studies revealed its crucial role in the development of cardiovascular fibrosis. In this study we examined IL-11 expression levels in the heart and the kidney exposed to high blood pressure in renovascular hypertensive rats and their correlations to fibrotic markers and kidney injury. METHODS: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats. IL-11 expression was measured by real-time polymerase chain reaction in the left ventricle and the right kidney. The correlation of cardiac IL-11 expression with biomarkers of renal fibrosis was assessed. We further investigated IL-11 expression in 2K1C rats grouped into rats with malignant vs. nonmalignant hypertension (distinguishing criteria: weight loss, number of fibrinoid necrosis, and onion skin lesions). RESULTS: Thirty-five days after clipping, mean arterial pressure was significantly increased in 2K1C. Renal IL-11 expression was elevated in 2K1C. In the heart there was only a trend toward higher IL-11 expression in 2K1C. IL-11 in the kidney in 2K1C correlated with the expression of transforming growth factor (TGF)-β1/2, collagens, fibronectin, osteopontin, as well as tissue inhibitors of metalloprotease 1/2. There were also correlations of IL-11 with tissue collagen expansion, number of activated fibroblasts and serum creatinine, but no correlation with mean arterial pressure. Renal expression of IL-11 was highest in rats with malignant hypertension. CONCLUSIONS: Renal IL-11 expression of renovascular hypertensive rats is markedly increased and correlates with profibrotic markers and loss of function and might therefore serve as a biomarker for the severity of hypertensive nephrosclerosis.
CRIS-Team Scopus Importer:2020-04-14
Keywords: blood pressure; hypertension; interleukin-11 (IL-11); malignant hypertension; renal fibrosis; two-kidney one-clip renovascular hypertension (2K1C)

DIFFERENT FORMS OF AFFERENT NERVE INPUT IN CARDIAC AND RENAL DISEASE IN RATS? - Rodionova, Kristina; Ditting, Tilmann; Pickny, Lisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Does renal artery supply indicate treatment success of renal denervation? - Schmid, Axel; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Schmieder, Roland; Uder, Michael; Ott, Christian (Cardiovascular and Interventional Radiology, 2013)
Purpose: Renal denervation (RDN) emerged as an innovative interventional antihypertensive therapy. With the exception of pretreatment blood pressure (BP) level, no other clear predictor for treatment efficacy is yet known. We analyzed whether the presence of multiple renal arteries has an impact on BP reduction after RDN. Methods: Fifty-three patients with treatment-resistant hypertension (office BP ≥ 140/90 mmHg and 24-h ambulatory BP monitoring (≥130/80 mmHg) underwent bilateral catheter-based RDN. Patients were stratified into one-vessel (OV) (both sides) and at least multivessel (MV) supply at one side. Both groups were treated on one vessel at each side; in case of multiple arteries, only the dominant artery was treated on each side. Results: Baseline clinical characteristics (including BP, age, and estimated glomerular filtration rate) did not differ between patients with OV (n = 32) and MV (n = 21). Office BP was significantly reduced in both groups at 3 months (systolic: OV -15 ± 23 vs. MV -16 ± 20 mmHg; diastolic: OV -10 ± 12 vs. MV -8 ± 11 mmHg, both p = NS) as well as 6 months (systolic: OV -18 ± 18 vs. MV -17 ± 22 mmHg; diastolic: OV -10 ± 10 vs. -10 ± 12 mmHg, both p = NS) after RDN. There was no difference in responder rate (rate of patients with office systolic BP reduction of at least 10 mmHg after 6 months) between the groups. Conclusion: In patients with multiple renal arteries, RDN of one renal artery - namely, the dominant one - is sufficient to induce BP reduction in treatment-resistant hypertension. © 2013 Springer Science+Business Media New York and the Cardiovascular and Interventional Radiological Society of Europe (CIRSE).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Ablation; Artery; Endovascular treatment; Hypertension; Kidney/renal; Radiofrequency ablation

EFFECTS OF NEUROGENIC CGRP ON RENAL AFFERENT PEPTIDERGIC NEURONS - Veelken, Roland; Raschke, Giulia; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Rodionova, Kristina (2018)
EVALuna2:204843

Effects of renal denervation on blood pressure in hypertensive patients with end-stage renal disease: a single centre experience - Ott, Christian; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical and Experimental Nephrology, 2019)
Background: Sympathetic nerve activity is a hallmark of hypertension in end-stage renal disease (ESRD). An initial proof-of-concept study implies that renal denervation (RDN) is feasible and safe in RDN, but overall data are limited. Methods: In this single-centre prospective pilot study six patients with ESRD and treatment resistant hypertension were consecutively included. Ambulatory blood pressure (ABP) was measured before and 6 months after RDN (Symplictiy Flex™, Medtronic Inc., Santa Rosa, CA). Moreover, haemodialysis parameters which may affect BP reduction were monitored closely. Results: In all patients bilateral RDN was successful done, without documentation of peri- or postprocedural complications. There was a significant reduction in 24-h ABP by 20 ± 17/15 ± 12 mmHg 6 months after RDN (systolic: 163 ± 16 versus 143 ± 9 mmHg, p = 0.043; diastolic: 96 ± 9 versus 81 ± 15 mmHg, p = 0.043), with similar results for day-, and nighttime values, respectively. Antihypertensive medication was kept stable as well as there was no change in haemodialysis parameters during follow-up. In addition, ultrafiltration/week (1.4 ± 1.4 versus 2.2 ± 1.4 l, p = 0.08) as well as hematocrit (measured at baseline and 6 months after RDN) (33.7 ± 4.3 versus 33.1 ± 3.9%, p = 0.715) revealed no change in volume status. Conclusion: Our single-centre pilot study not only supports current data on renal safety of RDN even in small arteries of patients with ESRD, but also enhances the knowledge towards an effective ABP reduction in this type of hypertensive patients.
CRIS-Team Scopus Importer:2019-05-07
Keywords: End-stage renal disease; Renal denervation; Treatment resistant hypertension

EFFECTS OF RENAL DENERVATION ON BLOOD PRESSURE IN PATIENTS WITH END-STAGE RENAL DISEASE: A SINGLE CENTER EXPERIENCE - Ott, C.; Schmid, Axel; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2018)
EVALuna2:202966

High Sodium Diet - Role in Renal Sympathodepression - Rodionova, Kristina; Ditting, Tilmann; Fahrmeier, Franziska; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (FASEB JOURNAL, 2020)
CRIS-Team WoS Importer:2020-10-16

Impact of renal denervation on tissue Na(+) content in treatment-resistant hypertension - Ott, Christian; Kopp, Christoph; Dahlmann, Anke; Schmid, Andrea; Linz, Peter; Hammon, Matthias; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Titze, Jens; Schmieder, Roland; Cavallaro, Alexander Josef (Clinical Research in Cardiology, 2017)
Renal denervation (RDN) has been introduced for reducing blood pressure (BP) in treatment-resistant hypertension (TRH). The precise mechanism how RDN exerts its BP-lowering effects are not yet fully understood. It is widely accepted that sodium (Na(+)) plays a crucial role in the pathogenesis of hypertensive disease. However, there is increasing evidence of osmotically inactive Na(+) storage. We investigated the impact of RDN on Na(+) homeostasis using estimation of salt intake, and measurement of tissue Na(+) content.In a study 41 patients with TRH (office BP >=140/90 mmHg and diagnosis confirmed by 24-h ambulatory BP monitoring) underwent RDN. Tissue Na(+) content was assessed non-invasively with 3.0 T magnetic resonance imaging before and 6 months after RDN. In addition, 24-h urinary Na(+) excretion as an estimate of salt intake and spot urine Na(+)/K(+) excretion were assessed. The study was registered at http://www.clinicaltrials.gov (ID: NCT01687725).There was a significant fall in BP (office: -17 ± 20/-10 ± 12 mmHg; 24-h: -11 ± 13/-6 ± 9 mmHg, all p < 0.001) 6 months after RDN. In contrast, tissue Na(+) content of the muscle (20.1 ± 3.9 vs. 20.7 ± 4.0 mmol/L, p = 0.229) and skin (24.4 ± 6.5 vs. 24.8 ± 6.6 mmol/L, p = 0.695) did not change after RDN. Moreover, there was also no change in salt intake after RDN, whereas Na(+)/K(+) ratio only acutely increased.Although RDN resulted in a substantial reduction of BP, tissue Na(+) content of the muscle and skin was not mobilized and reduced. These data indicate that the BP reduction after RDN is unrelated to Na(+) homeostasis.
EVALuna2:3743

Impaired excitability of renal afferent innervation after exposure to the inflammatory chemokine CXCL1 - Ditting, Tilmann; Freisinger, Wolfgang; Rodionova, Kristina; Schatz, Johannes; Lale, Nena; Heinlein, Sonja; Linz, Peter; Ott, Christian; Schmieder, Roland; Scrogin, Karie E.; Veelken, Roland (American Journal of Physiology-Renal Physiology, 2016)
Recently, we showed that renal afferent neurons exhibit a unique firing pattern, i.e., predominantly sustained firing, upon stimulation. Pathological conditions such as renal inflammation likely alter excitability of renal afferent neurons. Here, we tested whether the proinflammatory chemokine CXCL1 alters the firing pattern of renal afferent neurons. Rat dorsal root ganglion neurons (Th11-L2), retrogradely labeled with dicarbocyanine dye, were incubated with CXCL1 (20 h) or vehicle before patch-clamp recording. The firing pattern of neurons was characterized as tonic, i.e., sustained action potential (AP) firing, or phasic, i.e., <5 APs following current injection. Of the labeled renal afferents treated with vehicle, 58.9% exhibited a tonic firing pattern vs. 7.8%, in unlabeled, nonrenal neurons (P < 0.05). However, after exposure to CXCL1, significantly more phasic neurons were found among labeled renal neurons; hence the occurrence of tonic neurons with sustained firing upon electrical stimulation decreased (35.6 vs. 58.9%, P < 0.05). The firing frequency among tonic neurons was not statistically different between control and CXCL1-treated neurons. However, the lower firing frequency of phasic neurons was even further decreased with CXCL1 exposure [control: 1 AP/600 ms (1-2) vs. CXCL1: 1 AP/600 ms (1-1); P < 0.05; median (25th-75th percentile)]. Hence, CXCL1 shifted the firing pattern of renal afferents from a predominantly tonic to a more phasic firing pattern, suggesting that CXCL1 reduced the sensitivity of renal afferent units upon stimulation.
EVALuna2:3740

Impaired Neovascularization and Reduced Capillary Supply in the Malignant vs. Non-malignant Course of Experimental Renovascular Hypertension - Jagusch, Lisa Gudrun; Cordasic, Nada; Amann, Kerstin Ute; Veelken, Roland; Jacobi, Johannes; Hilgers, Karl Friedrich; Hartner, Andrea (Frontiers in Physiology, 2016)
Malignant hypertension develops in some cases of hypertension but not in others. We hypothesized that an impaired neovascularization and a reduced capillary supply characterizes the malignant course of experimental hypertension. Two-kidney, one-clip renovascular hypertension was induced in rats; controls (sham) were sham operated. To distinguish malignant hypertension from non-malignant hypertension, we considered two factors: weight loss, and the number of typical vascular lesions (onion skin lesions and fibrinoid necroses) per kidney section of the nonclipped kidney. Animals in the upper half for both criteria were defined as malignant hypertensives. After 5 weeks, mean arterial blood pressure was elevated to the same degree in malignant hypertension and non-malignant hypertension whereas plasma renin and aldosterone were significantly higher in malignant hypertensives. The expression of plasminogen activator inhibitor-1 was elevated (up to 14-fold) in non-malignant but significantly more increased (up to 36-fold) in malignant hypertensive rats, compared to sham. As a bioassay for neovascularization, the area of granulation tissue ingrowth in polyvinyl discs (implanted subcutaneously) was reduced in malignant hypertension compared to non-malignant hypertension and sham, while there was no difference between non-malignant hypertension and sham. The number of renal and left ventricular capillaries was significantly lower in malignant hypertension compared to non-malignant hypertension, as was the number of proliferating endothelial cells. We conclude that an impaired neovascularization and capillarization occurs in malignant renovascular hypertension but not in the non-malignant course of the disease despite comparable blood pressure levels. This might contribute to the unique vascular lesions and progressive target organ damage observed in malignant hypertension.
EVALuna2:3914

Improvement of albuminuria after renal denervation - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Ewen, Sebastian; Ukena, Christian; Uder, Michael; Boehm, Michael; Schmieder, Roland (International Journal of Cardiology, 2014)
The primary objective of this study was the effect of renal denervation (RDN) on elevated urinary albumin-to-creatinine ratio (UACR) in treatment-resistant hypertensive patients. In addition, patients were stratified according their UACR at baseline into micro- (30-300 mg/g, n=37) and macroalbuminuria (>= 300 mg/g, <2,200 mg/g, n=22).Increased albuminuria indicates cardiovascular and renal damage in hypertension. RDN emerged as an innovative interventional approach to reduce blood pressure (BP) and may thus reduce albumin urinary excretion.Fifty-nine treatment-resistant hypertensive patients with elevated UACR at baseline underwent catheter-based RDN using the Symplicity Flex(TM) catheter (Medtronic Inc., Santa Rosa, CA).In the whole and pre-specified subgroups both office and 24-h ambulatory BP were significantly reduced 6 months after RDN. In parallel, a significant reduction in UACR occurred in all patients (160 (65-496) versus 89 (29-319) mg/g creatinine, p<0.001) and in both subgroups (microalbuminuria: 83 (49-153) versus 58 (17-113) mg/g creatinine, p=0.001; macroalbuminuria: (536 (434-1483) versus 478 (109-1080) mg/g creatinine, p<0.001). In accordance, the prevalence of micro- and macroalbuminuria decreased significantly. Regression analysis revealed a modest positive relationship between the decrease of UACR and the fall of systolic BP (?=0.340, p=0.039) independent of renal function. Renal function remained unchanged after RDN.In summary, following RDN, the magnitude of albuminuria as well as the prevalence of micro- and macroalbuminuria decreased in treatment-resistant hypertensive patients. Since albuminuria is an independent renal and cardiovascular risk factor, our findings suggest a reduction of renal and cardiovascular risk in these patients.
EVALuna2:3681

INTRARENAL HIGH SALT ADMINISTRATION CAUSES TONIC INHIBITION OF RENAL SYMPATHETIC NERVE ACTIVITY (RSNA) - Hindermann, Martin; Rodionova, Kristina; Dietz, Amelie; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Veelken, Roland (2018)
EVALuna2:204842

Mid-Term Vascular Safety of Renal Denervation Assessed by Follow-up MR Imaging. - Schmid, Axel; Schmieder, Raphael; Lell, Michael; Janka, Rolf Matthias; Veelken, Roland; Schmieder, Roland; Uder, Michael; Ott, Christian (Cardiovascular and Interventional Radiology, 2016)
Renal denervation (RDN) emerged as a treatment option for reducing blood pressure (BP) in patients with treatment-resistant hypertension (TRH). However, concerns have been raised regarding the incidence of late renal artery stenosis or thromboembolism after RDN. The goal of the current study was, therefore, to conduct a prospective clinical trial on the mid-term vascular integrity of the renal arteries and the perfusion of the renal parenchyma assessed by magnetic resonance imaging (MRI) in the follow-up after catheter-based RDN.In our single-centre investigator initiated study, 51 patients with true TRH underwent catheter-based RDN using the Symplicity Flex(TM) catheter (Medtronic Inc., Palo Alto, CA). Follow-up MRI was performed at a median of 11 months (interquartile range 6-18 months) after RDN on a 1.5T MR unit. High-resolution MR angiography (MRA) and MRI results were compared to the baseline digital angiography of renal arteries obtained at time of RDN. In case of uncertainties (N = 2) catheter angiography was repeated.Both office and 24-h ambulatory BP were significantly reduced 6 and 12 months after RDN. Renal function remained unchanged 6 and 12 months after RDN. In all patients, MRA excluded new or progression of pre-existing low grade renal artery stenosis as well as focal aneurysms at the sites of radiofrequency ablation. In none of the patients new segmental perfusion deficits in either kidney were detected on MRI.No vascular or parenchymal complications after radiofrequency-based RDN were detected in 51 patients followed up by MRI.
EVALuna2:3794

NCX1 represents an ionic Na+ sensing mechanism in macrophages - Neubert, Patrick; Homann, Arne; Wendelborn, David; Bär, Anna Lorena; Krampert, Luka; Trum, Maximilian; Schröder, Agnes; Ebner, Stefan; Weichselbaum, Andrea; Schatz, Valentin; Linz, Peter; Veelken, Roland; et al. (Plos Biology, 2020)
Inflammation and infection can trigger local tissue Na+ accumulation. This Na+-rich environment boosts proinflammatory activation of monocyte/macrophage-like cells (MΦs) and their antimicrobial activity. Enhanced Na+-driven MΦ function requires the osmoprotective transcription factor nuclear factor of activated T cells 5 (NFAT5), which augments nitric oxide (NO) production and contributes to increased autophagy. However, the mechanism of Na+ sensing in MΦs remained unclear. High extracellular Na+ levels (high salt [HS]) trigger a substantial Na+ influx and Ca2+ loss. Here, we show that the Na+/Ca2+ exchanger 1 (NCX1, also known as solute carrier family 8 member A1 [SLC8A1]) plays a critical role in HS-triggered Na+ influx, concomitant Ca2+ efflux, and subsequent augmented NFAT5 accumulation. Moreover, interfering with NCX1 activity impairs HS-boosted inflammatory signaling, infection-triggered autolysosome formation, and subsequent antibacterial activity. Taken together, this demonstrates that NCX1 is able to sense Na+ and is required for amplifying inflammatory and antimicrobial MΦ responses upon HS exposure. Manipulating NCX1 offers a new strategy to regulate MΦ function.
CRIS-Team Scopus Importer:2020-07-03

Neurogenic substance P-influences on action potential production in afferent neurons of the kidney? - Rodionova, Kristina; Hilgers, Karl Friedrich; Linz, Peter; Schaetzl, Johannes; Raschke, Giulia; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2021)
We recently showed that a substance P (SP)-dependent sympatho-inhibitory mechanism via afferent renal nerves is impaired in mesangioproliferative nephritis. Therefore, we tested the hypothesis that SP released from renal afferents inhibits the action potential (AP) production in their dorsal root ganglion (DRG) neurons. Cultured DRG neurons (Th11-L2) were investigated in current clamp mode to assess AP generation during both TRPV1 stimulation by protons (pH 6) and current injections with and without exposure to SP (0.5 mu mol) or CGRP (0.5 mu mol). Neurons were classified as tonic (sustained AP generation) or phasic (<= 4 APs) upon current injection; voltage clamp experiments were performed for the investigation of TRPV1-mediated inward currents due to proton stimulation. Superfusion of renal neurons with protons and SP increased the number of action potentials in tonic neurons (9.6 +/- 5 APs/10 s vs. 16.9 +/- 6.1 APs/10 s, P < 0.05, mean +/- SD, n = 7), while current injections with SP decreased it (15.2 +/- 6 APs/600 ms vs. 10.2 +/- 8 APs/600 ms, P < 0.05, mean +/- SD, n = 29). Addition of SP significantly reduced acid-induced TRPV1-mediated currents in renal tonic neurons (- 518 +/- 743 pA due to pH 6 superfusion vs. - 82 +/- 50 pA due to pH 6 with SP superfusion). In conclusion, SP increased action potential production via a TRPV1-dependent mechanism in acid-sensitive renal neurons. On the other hand, current injection in the presence of SP led to decreased action potential production. Thus, the peptide SP modulates signaling pathways in renal neurons in an unexpected manner leading to both stimulation and inhibition of renal neuronal activity in different (e.g., acidic) environmental contexts.
CRIS-Team WoS Importer:2021-04-16

Neurogenic tachykinin mechanisms in experimental nephritis of rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Paulus, Eva-Maria; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2020)
We demonstrated earlier that renal afferent pathways combine very likely "classical" neural signal transduction to the central nervous system and a substance P (SP)-dependent mechanism to control sympathetic activity. SP content of afferent sensory neurons is known to mediate neurogenic inflammation upon release. We tested the hypothesis that alterations in SP-dependent mechanisms of renal innervation contribute to experimental nephritis. Nephritis was induced by OX-7 antibodies in rats, 6 days later instrumented for recording of blood pressure (BP), heart rate (HR), drug administration, and intrarenal administration (IRA) of the TRPV1 agonist capsaicin to stimulate afferent renal nerve pathways containing SP and electrodes for renal sympathetic nerve activity (RSNA). The presence of the SP receptor NK-1 on renal immune cells was assessed by FACS. IRA capsaicin decreased RSNA from 62.4 +/- 5.1 to 21.6 +/- 1.5 mV s (*p < 0.05) in controls, a response impaired in nephritis. Suppressed RSNA transiently but completely recovered after systemic administration of a neurokinin 1 (NK1-R) blocker. NK-1 receptors occurred mainly on CD11(+)dendritic cells (DCs). An enhanced frequency of CD11c(+)NK1R(+)cell, NK-1 receptor(+)macrophages, and DCs was assessed in nephritis. Administration of the NK-1R antagonist aprepitant during nephritis reduced CD11c(+)NK1R(+)cells, macrophage infiltration, renal expression of chemokines, and markers of sclerosis. Hence, SP promoted renal inflammation by weakening sympathoinhibitory mechanisms, while at the same time, substance SP released intrarenally from afferent nerve fibers aggravated immunological processes i.e. by the recruitment of DCs.
CRIS-Team WoS Importer:2020-11-06

No benefit of HIF prolyl hydroxylase inhibition for hypertensive renal damage in renovascular hypertensive rats - Hartner, Andrea; Dambietz, Thomas; Cordasic, Nada; Willam, Carsten; Burzlaff, Nicolai; Brötsch, Martin; Daniel, Christoph; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Schley, Gunnar; Hilgers, Karl Friedrich (Frontiers in Physiology, 2023)
Introduction: We previously reported that malignant hypertension is associated with impaired capillary density of target organs. Here, we tested the hypothesis that stabilization of hypoxia-inducible factor (HIF) in a modified “preconditioning” approach prevents the development of malignant hypertension. To stabilize HIF, we employed pharmacological inhibition of HIF prolyl hydroxylases (PHD), that profoundly affect HIF metabolism. Methods: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats; controls were sham operated. 2K1C rats received either intermittent injections of the PHD inhibitor ICA (2-(1-chloro-4-hydroxyisoquinoline-3-carboxamido) acetate) or placebo. Thirty-five days after clipping, the frequency of malignant hypertension was assessed (based on weight loss and the occurrence of characteristic vascular lesions). In addition, kidney injury was compared between all ICA treated versus all placebo treated 2K1C, regardless of the occurrence of malignant hypertension. HIF stabilization was evaluated by immunohistochemistry, and HIF target gene expression by RT-PCR. Results: Blood pressure was elevated to the same degree in ICA- and placebo-treated 2K1C compared to control rats. ICA treatment did not affect the frequency of malignant hypertension or the extent of kidney tissue fibrosis, inflammation, or capillary density. There was a trend towards higher mortality and worse kidney function in ICA-treated 2K1C rats. ICA increased the number of HIF-1α-positive renal tubular cell nuclei and induced several HIF-1 target genes. In contrast, expression of HIF-2α protein as well as HIF-2 target genes were markedly enhanced by 2K1C hypertension, irrespective of ICA treatment. Discussion: We conclude that intermittent PHD inhibition did not ameliorate severe renovascular hypertension in rats. We speculate that the unexpected strong renal accumulation of HIF-2α in renovascular hypertension, which could not be further augmented by ICA, may contribute to the lack of a benefit from PHD inhibition.
CRIS-Team Scopus Importer:2023-07-21
Keywords: capillarization; HIF stabilization; malignant hypertension; renovascular; vascular lesions

OS 28-03 SECRETORY CAPACITY OF PANCREATIC BETA CELLS IS ENHANCED 6 MONTHS AFTER RENAL DENERVATION IN TREATMENT RESISTANT HYPERTENSIVE PATIENTS - Ott, Christian; Kistner, Iris; Schmid, Axel; Friedrich, Stefanie; Ditting, Tilmann; Veelken, Roland; Mahfoud, Felix; Boehm, Michael; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2016)
Renal denervation (RDN) lowers blood pressure (BP) by interruption of sympathetic nerve activity. A high sympathetic tone increases not only BP but also decreases pancreatic beta cell insulin secretion. Hence, the objective of the study was to analyze whether RDN improves secretory capacity of beta cells.In 40 patients (7 diabetics, 19 prediabetics, 14 non diabetics) with treatment resistant hypertension (defined by office BP >= 140/90 mmHg and diagnosis confirmed with 24-h ambulatory BP >= 130/80 mmHg), insulin secretion was measured before and 6 months after RDN (Simplicity flex catheter, Medtronic) by glucagon test. At each time point blood was sampled prior to glucagon administration and 6 minutes after intravenous injection of 1 ml glucagon for measurement of C-peptide, insulin and proinsulin (by ELISA).In these 40 patients (mean age 58 ± 12 years, mean office BP 154 ± 22 mmHg / 89 ± 14 mmHg while on 5.2 ± 1.4 antihypertensive drugs) office systolic and diastolic BP was significantly reduced 6 months after RDN (both p < 0.01). Fasting plasma glucose and HbA1c level was significantly reduced 6 month after RDN (both p < 0.01). Six months after RDN, the increase of C-peptide concentration and insulin concentration after glucagon injection was significantly higher compared to before RDN (both p < 0.05).Thus, our data indicate an improved pancreatic beta cell function after RDN in patients with treatment resistant hypertension.
EVALuna2:14605

Patient preference for therapies in hypertension: a cross-sectional survey of German patients - Schmieder, Roland; Högerl, Karin; Jung, Susan; Bramlage, Peter; Veelken, Roland; Ott, Christian (Clinical Research in Cardiology, 2019)
BACKGROUND: Hypertension is poorly controlled in numerous patients despite effective medication being available. Catheter-based renal denervation (RDN) has emerged as an alternative treatment option. We aimed to assess how likely patients with elevated blood pressure (BP) are to accept RDN as treatment option. METHODS: A questionnaire-based cross-sectional survey was performed in patients with elevated BP in Germany. Data on patient demographics, clinical characteristics and treatment preferences were collected, anonymized and analyzed. RESULTS: One thousand and eleven patients completed the survey. Mean age was 66 years (55% male). If not already on medication (n = 172), 38.2% of patients would prefer RDN. Of those already on drug therapy (n = 839), 28.2% would opt for RDN. Patients who were pro-RDN were younger (p < 0.0001) and more often male (p < 0.0001). Nineteen percent would choose RDN if it lowered systolic BP by at least 20 mmHg, more than 40% if they did not have to take any more pills thereafter, and 30% if it would lower BP by at least 10 mmHg. Experiences of side effects and drug adherence were identified as determinants of patient preference. Physicians were the main source of information regarding medical problems (95.5%) and influence patients' decision regarding therapies (98%). CONCLUSIONS: This survey found that a significant proportion of patients would choose catheter-based RDN over lifelong pharmacotherapy. These patients were younger and more likely to be male but their expectation of the extent of BP decrease with RDN was high. Physicians are key mediators for treatment selection. They need to incorporate patient preferences into shared decision making.
EVALuna2:118640

Renal denervation-implications for chronic kidney disease - Veelken, Roland; Schmieder, Roland (Nature Reviews Nephrology, 2014)
Catheter-based renal denervation to treat patients with resistant hypertension and chronic kidney disease (CKD) has generated considerable interest. Data from the majority of, but not all, observational studies and randomized controlled trials suggest that the procedure does not impair renal function and can effectively reduce office and ambulatory blood pressure in patients with primary hypertension. The putative beneficial effects of renal denervation seem to result from the interruption of renal efferent and afferent nerves. In patients with resistant hypertension and CKD, interruption of afferent reflexes might lead to a reduction in global sympathetic tone. The subsequent sustained reduction in blood pressure is expected to slow the progression of renal disease. However, renal denervation might also improve glucose metabolism, increase insulin sensitivity and reduce renal inflammation, with renoprotective effects in patients with CKD. Additional large randomized controlled trials of renal denervation in hypertensive and normotensive patients with CKD are required to precisely define the clinical value of the procedure in this population.
EVALuna2:3684

Renal denervation in moderate treatment-resistant hypertension - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Spies, Aline; Ukena, Christian; Laufs, Ulrich; Uder, Michael; Boehm, Michael; Schmieder, Roland (Journal of the American College of Cardiology, 2013)
Objectives This study sought to investigate the effect of renal denervation (RDN) in patients with treatment-resistant hypertension according to the established definition (Joint National Committee VII and European Society of Hypertension/European Society of Cardiology guidelines), that is, office blood pressure (BP) ≥140/90 mm Hg (with at least three antihypertensive drugs, including a diuretic, in adequate doses) and confirmed by 24-h ambulatory BP monitoring (ABPM). Background RDN emerged as an innovative interventional antihypertensive therapy. However, so far, only patients with severe hypertension (systolic BP ≥160 mm Hg or ≥150 mm Hg for patients with type 2 diabetes) have been investigated. Methods In this study, there were 54 patients with moderate treatment-resistant hypertension (office BP ≥140/90 mm Hg and <160/100 mm Hg and diagnosis confirmed by 24-h ABPM of ≥130/80 mm Hg) who underwent catheter-based RDN using the Symplicity catheter (Medtronic Inc., Mountain View, California). Results Patients were treated with 5.1 ± 1.4 antihypertensive drugs on average. Office BP was significantly reduced by 13/7 mm Hg 6 months after RDN (systolic: 151 ± 6 mm Hg vs. 138 ± 21 mm Hg, p < 0.001; diastolic: 83 ± 11 mm Hg vs. 75 ± 11 mm Hg, p < 0.001). In patients (n = 36) who underwent ABPM 6 months after treatment, there was a reduction in average 24-h ABPM by 14/7 mm Hg (systolic: 150 ± 16 mm Hg vs. 136 ± 16 mm Hg, p < 0.001; diastolic: 83 ± 10 mm Hg vs. 76 ± 10 mm Hg, p < 0.001). In 51% of patients, office BP was controlled below 140/90 mm Hg after RDN. In addition, heart rate decreased from 67 ± 11 to 63 ± 10 beats/min (p = 0.006). Conclusions Our data indicate that RDN may reduce office and 24-h ambulatory BP substantially in patients with moderate treatment-resistant hypertension. (Renal Denervation in Treatment Resistant Hypertension; NCT01687725). © 2013 by the American College of Cardiology Foundation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 24-h ambulatory blood pressure; renal denervation; treatment-resistant hypertension

Renal denervation preserves renal function in patients with chronic kidney disease and resistant hypertension - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Toennes, Stefan W.; Ewen, Sebastian; Ditting, Tilmann; Veelken, Roland; Ukena, Christian; Uder, Michael; Boehm, Michael; Schmieder, Roland (Journal of Hypertension, 2015)
Arterial hypertension and increased sympathetic activity are underlying pathogenetic mechanisms of the progressive loss of renal function in patients with chronic kidney disease (CKD). Meta-analyses have shown that impaired renal function is an independent cardiovascular risk factor. We hypothesized that renal denervation (RDN) decreases the decline of renal function in patients with CKD stages 3 and 4 and treatment-resistant hypertension.We performed an observational study of 27 patients with CKD stages 3 and 4, office blood pressure (BP) >= 140/90 mmHg, while on at least three antihypertensive drug classes including diuretic, and diagnosis confirmed by 24-h ambulatory BP measurement >= 130/80 mmHg. All patients underwent catheter-based RDN using the Symplicity Flex RDN System (Medtronic Inc., Santa Rosa, California, USA). Renal function was evaluated for up to 3 years prior and 1 year after RDN. The change in estimated glomerular filtration rate (eGFR) was calculated by regression slope individually for each patient before and after RDN. The study was registered at http://www.clinicaltrials.gov (ID: NCT01442883).Mean baseline BP was 156 ± 12/82 ± 13 mmHg, despite treatment with 6.2 ± 1.1 antihypertensive drugs. One year after RDN, office BP was reduced by 20 ± 20 (P < 0.001)/8 ± 14 mmHg (P = 0.005) and average 24-h ambulatory BP by 9 ± 14 (P = 0.009)/4 ± 7 mmHg (P = 0.019). Before RDN, eGFR declined by -4.8 ± 3.8 ml/min per 1.73 m per year, and after RDN eGFR improved by +1.5 ± 10 ml/min per 1.73 m at 12 months (P = 0.009).Our observational pilot study in patients with CKD stages 3 and 4 indicates that treatment of hypertension with RDN decreases BP and slows or even halts the decline of renal function.
EVALuna2:3767

RENAL HEMODYNAMIC CHANGES AFTER RENAL DENERVATION - Schmieder, R. S.; Schmid, Axel; Janka, Rolf Matthias; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland; Ott, Christian (2016)
EVALuna2:34706

Responsiveness of afferent renal nerve units in renovascular hypertension in rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Rafii-Tabrizi, Salman; Doellner, Johannes; Cordasic, Nada; Linz, Peter; Karl, Annalena; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; et al. (Pflügers Archiv: European Journal of Physiology, 2021)
Previous data suggest that renal afferent nerve activity is increased in hypertension exerting sympathoexcitatory effects. Hence, we wanted to test the hypothesis that in renovascular hypertension, the activity of dorsal root ganglion (DRG) neurons with afferent projections from the kidneys is augmented depending on the degree of intrarenal inflammation. For comparison, a nonhypertensive model of mesangioproliferative nephritis was investigated. Renovascular hypertension (2-kidney, 1-clip [2K1C]) was induced by unilateral clipping of the left renal artery and mesangioproliferative glomerulonephritis (anti-Thy1.1) by IV injection of a 1.75-mg/kg BW OX-7 antibody. Neuronal labeling (dicarbocyanine dye [DiI]) in all rats allowed identification of renal afferent dorsal root ganglion (DRG) neurons. A current clamp was used to characterize neurons as tonic (sustained action potential [AP] firing) or phasic (1-4 AP) upon stimulation by current injection. All kidneys were investigated using standard morphological techniques. DRG neurons exhibited less often tonic response if in vivo axonal input from clipped kidneys was received (30.4% vs. 61.2% control, p < 0.05). However, if the nerves to the left clipped kidneys were cut 7 days prior to investigation, the number of tonic renal neurons completely recovered to well above control levels. Interestingly, electrophysiological properties of neurons that had in vivo axons from the right non-clipped kidneys were not distinguishable from controls. Renal DRG neurons from nephritic rats also showed less often tonic activity upon current injection (43.4% vs. 64.8% control, p < 0.05). Putative sympathoexcitatory and impaired sympathoinhibitory renal afferent nerve fibers probably contribute to increased sympathetic activity in 2K1C hypertension.
CRIS-Team WoS Importer:2021-07-23

Retinal microperfusion after renal denervation in treatment-resistant hypertensive patients - Ott, Christian; Harazny, Joanna M.; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Bladowski, Marek; Michelson, Georg; Uder, Michael; Schmieder, Roland (Clinical Research in Cardiology, 2015)
High pulsatile pressure and flow in the arteries causes microvascular damage, and hence increased cardio-, and cerebrovascular complications. With advanced stages of hypertensive disease, an exaggerated pulsatile retinal capillary flow (RCF) has been shown, but data about interventional effect are missing.Fifty-one patients with true treatment-resistant hypertension (TRH) underwent renal denervation (RDN) using the Symplicity Flex(TM) catheter and were followed for 12 months. RCF was assessed non-invasively using Scanning laser Doppler flowmetry (SLDF) before, 6 (6 M), and 12 (12 M) months after RDN. RCF was measured in systole and diastole and pulsed RCF (difference of RCF in systole minus diastole) was calculated. In addition, flicker light-induced vasodilation (representing vasodilatory capacity) was assessed.Systolic and diastolic office blood pressure (BP) as well as 24-h ABPM decreased significantly 6 M and 12 M after RDN, compared to baseline values (all p < 0.001). There was a significant reduction of pulsed RCF 6 M (231 ± 81 versus 208 ± 68 AU, p = 0.046) and 12 M (194 ± 72 AU, p = 0.001) after RDN, whereas the mean RCF was unchanged. Moreover, there was a significant increase of flicker light-induced vasodilation after RDN (p = 0.043).In hypertensive patients with TRH, we observed a decrease of pulsed RCF 6 M and 12 M after RDN and an increase of vasodilatory capacity, in parallel to decreases in BP and heart rate. The reduction of pulsed RCF after RDN implies a decrease of shear stress on the vascular wall by the pulsed blood flow. This and the increment of vasodilatory capacity suggest an improvement of retinal (and potentially cerebral) microcirculation.
EVALuna2:3762

Secretory Capacity of Pancreatic Beta-Cells Is Enhanced 6 Months After Renal Denervation in Hypertensive Patients - Ott, Christian; Schmid, Axel; Mahfoud, Felix; Akarca, Ertan; Kistner, Iris; Ditting, Tilmann; Veelken, Roland; Boehm, Michael; Uder, Michael; Schmieder, Roland (Journal of the American College of Cardiology, 2018)
EVALuna2:35226

The effect of renal denervation in moderate treatment-resistant hypertension with confirmed medication adherence - Ott, Christian; Mahfoud, Felix; Schmid, Andrea; Ewen, Sebastian; Toennes, Stefan W.; Meyer, Markus R.; Helfer, Andreas G.; Maurer, Hans H.; Ditting, Tilmann; Veelken, Roland; Zivanovic, Ina; Uder, Michael; et al. (Journal of Hypertension, 2016)
Data on the blood pressure (BP)-lowering effect of renal denervation (RDN) in moderate treatment-resistant hypertension (TRH) are limited. Moreover, change of adherence to medication, as one potential confounder of BP response, has never been analyzed rigorously in this group of patients. We analyzed the effect of RDN on BP in patients with moderate TRH who were retrospectively found to be completely adherent to their antihypertensive medication.Our study cohort comprised 40 patients with moderate TRH [office BP >= 140/90 but <160/100 mmHg and 24-h ambulatory BP monitoring (ABPM) >=130/80 mmHg] who underwent catheter-based RDN. Further major inclusion criterion was complete adherence to their medication (>=80% intake of their prescribed antihypertensive drugs) at baseline (assessed by retrospective toxicological analysis).Six months after RDN, office BP was reduced by -10/-6 mmHg (SBP: 149 ± 6 vs. 139 ± 15 mmHg; DBP: 81 ± 12 vs. 75 ± 10 mmHg; both P < 0.001) and 24-h ABPM by -7/-4 mmHg (SBP: 150 ± 14 vs. 143 ± 16 mmHg, P = 0.005; DBP: 82 ± 10 vs. 78 ± 9 mmHg, P = 0.009). Number of prescribed antihypertensive medication [6.0 (5.0-6.0) vs. 5.5 (5.0-6.0), P = 0.013] and adherence rate (95.2 ± 7.6 vs. 91.7 ± 13.9%, P = 0.065) was slightly reduced 6 months after RDN, both likely to underestimate the true BP reduction.Thus, our data indicate that even after given full respect to drug adherence as potential confounder of BP response after RDN, both office and 24-h ABPM were substantially reduced in patients with moderate TRH.
EVALuna2:3907

Vascular and renal hemodynamic changes after renal denervation - Ott, Christian; Janka, Rolf Matthias; Schmid, Axel; Titze, Stephanie; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical Journal of the American Society of Nephrology, 2013)
Background and objectives Renal denervation (RDN) has been shown to be effective in reducing BP in treatmentresistant hypertension. Measurement of the renal and sympathetic activity revealed a decrease in sympathetic drive to the kidney and small resistance vessels after RDN. However, the consequences on renal perfusion and renal vascular resistance (RVR), as well as central hemodynamics, are unknown. Design, setting, participants, & measurements Nineteen patients with treatment-resistant hypertension (office BP140/90mmHg, despite at least three antihypertensive drugs [including a diuretic], and diagnosis confirmed by 24-hour ambulatory BPmonitoring) underwent RDNbetween January andOctober 2011. Renal perfusion and RVR were noninvasively assessed by magnetic resonance imaging with arterial spin labeling, and renal function was assessed by estimating GFR before (day 21), after (day +1), and again after 3 months of RDN. Central hemodynamics was assessed using pulse wave analysis at day 21 and after 6 months of RDN. Results Peripheral office BP (systolic, 158±26 versus 142±23mmHg, P=0.002; diastolic, 83±13 versus 76±9mmHg, P=0.02) and mean systolic 24-hour ambulatory BP (159±17 versus 152±17 mmHg, P=0.02) were significantly reduced 6 months after RDN. Renal perfusion was not statistically different between day 21 and day +1 (256.8 [interquartile range (IQR), 241-278] versus 263.4 [IQR, 252-277] ml/min per 100 g; P=0.17) as well as after 3 months (256.8 [IQR, 241-278] versus 261.2 [IQR, 240-285] ml/min per 100 g; P=0.27) after RDN. RVR dropped (432.1 [IQR, 359-525] versus 390.6 [IQR, 338-461] AU; P=0.02), whereas renal function was not statistically different at any time point. Central systolic BP (145±31 versus 131628 mmHg; P=0.009), diastolic BP (85±18 versus 80±14 mmHg; P=0.03), and central pulse pressure (61±18 versus 52±18 mmHg; P=0.02) were significantly reduced 6 months after RDN. Central augmentation index (24±8 versus 20±8%; P=0.02) was decreased 6 months after RDN. Conclusion The data indicate that RDN significantly reduced peripheral and central BP. Despite reduced systemic BP, renal perfusion and function did not change after RDN. © 2013 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2023-03-08